THE SOCIAL RESPONSIBILITY OF MOROCCAN ENTERPRISES TOWARDS SUSTAINABLE PERFORMANCE:CSR STUDY COSUMAR SIDI BENNOUR - EL Gueddar O.E; Sahib-Eddine A (International Journal of Research Science and Management, 2017)
The globalization of the economy imposes a new order on the Moroccan company marked by the opening of markets and the appearance of new international competitors. One of the factors of differentiation is technological and organizational innovation. The company is then obliged to improve its management to ensure the necessary balance between these various expectations and the imperative need to sustain its performance to establish its legitimacy and creates lasting value. In this context, several companies are investing in the field of Corporate Social Responsibility (CSR) and are awarded the CGEM Label for CSR. This Label is a solemn recognition of Morocco's respect for their commitment to observe, defend and promote the universal principles of social responsibility and sustainable development in their economic activities, their social relations and, more generally, their contribution to the creation valuable. CSR thus enables the Moroccan company to take advantage of these opportunities and be up to the challenges imposed by this new context by integrating old and new principles and values and management practices to increase its Performance and its value created for it and its stakeholders.In this article, we study the CSR practices in the agri-food sector, considered the first sector of the national industry by studying the CSR practices of the Cosumar Sidi Bennour beneficiary of the CGEM CSR label.